Prevalencia de hipertensión arterial en la parroquia Punzara de la ciudad de Loja - Elizalde Medina, Johanna Elizabeth (2019)
High blood pressure (HBP) is a multifactorial disease occupying in Ecuador the sixth place with respect to the 10 main causes of mortality. The purpose of the study was to: identify the prevalence of hypertension according to grade, age group, gender; establish the main risk factors associated with hypertension and compare the risk factors of the global hypertensive population (constituted by diagnosed and undiagnosed hypertensive patients) with those of the non-hypertensive population of the Punzara parish. The study was of a descriptive, prospective cross-sectional type, with a sample of 380 participants; Based on the "Clinical Practice Guideline of the European Society of Hypertension (ESH) / European Society of Cardiology (ESC) 2018 for management of hypertension", blood pressure (BP) measurement was performed three times separated by a range of 1-2 minutes, a survey of 22 questions was applied, and anthropometric measurements were taken. As a result, a prevalence of HBP was obtained of 22.4%, 64% corresponding to the female sex and 36% to the male sex. In men aged 41-65 years and> 66 years, the prevalent BP levels were normal high pressure and normal pressure with 4.7% respectively; in women aged 41-65 years it was normal high pressure 9.4% and in> 66 years normal pressure 8.2%. The predominant risk factors were: body mass index (BMI)> 25, poor eating habits and low physical activity. It can evidence of the high prevalence of hypertension, and its main risk factors which are modifiable by adopting healthy lifestyle habits. Key words: blood pressure, risk factors, body mass index, physical activity.